A política de indexação na perspectiva do conhecimento organizacional - Rubi, Milena Polsinelli [UNESP] (2004)
The indexing policy must be constituted of pertaining strategies being appropriate to the information system retrieval objectives. That's because under the system viewpoint indexing is recognized as its most important part within the procedures carried on to treating information once it influences the results of searching strategies. The indexer has the primary function of understanding the document while carrying on a conceptual analysis that properly represents its contents so that correspondence occur between the index and the subject searched by users. For that, there are indexing manuals that must represent the information system indexing policy and the reality of the indexer work. However, due to scarce literature on indexing policy it was aimed to obtain more subsides on the subject through the indexer practical experience. Our operational objectives are: analyzing the indexer context and investigating his/her knowledge on indexing policy through the methodology of reading as a social event/verbal protocol in groups. Thus we can reach our final goal of trying to fill a theoretical gap on indexing policy. First, it was carried on a primary data collecting with three indexers in two university libraries in Marília - SP, that are not subordinate to any larger information system, on the areas of Medicine and Law. That collecting had as goals verifying the methodology applicability towards the ends of this thesis and serve as a model in relation to the way of method application and carrying on during data collecting. Afterwards, it was carried on a second data collecting with two indexers and two university libraries managers on the Dentistry area, considered basic centers by Sistema de Informação Especializado em Odontologia (SIEO) to which they are subordinate. The results obtained from the analysis... (Complete abstract, click electronic address below)